Heat Shock Protein 90 Inhibitor (17-AAG) Induces Apoptosis and Decreases Cell Migration/Motility of Keloid Fibroblasts. Issue 1 (July 2015) - Yun, In Sik; Lee, Mi Hee; Rah, Dong Kyun; Lew, Dae Hyun; Park, Jong-Chul; Lee, Won Jai
Abstract : Background: The regulation of apoptosis, proliferation, and migration of fibroblasts is altered in keloids. The 90-kDa heat shock protein (heat shock protein 90) is known to play a key role in such regulation. Therefore, the authors investigated whether the inhibition of heat shock protein 90 in keloid fibroblasts could induce apoptosis and attenuate keloid fibroblast proliferation and migration. Methods: The authors evaluated heat shock protein 90 expression in keloid tissues with immunohistochemistry. The authors used cell viability [3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide] assays and annexin V/propidium iodide staining for apoptosis, a wound healing model and cell tracking system to assess cell migration, and Akt Western blotting analysis in keloid fibroblasts after inhibition of heat shock protein 90 with 17-allylaminodemethoxygeldanamycin (17-AAG). Results: The expression of heat shock protein 90 in keloid tissues was significantly increased compared with normal tissues. The 17-AAG–treated keloid fibroblasts showed significantly decreased proliferation, promotion of apoptosis, and decreased expression of Akt. Furthermore, a dose-dependent decrease in cell migration was noted after 17-AAG treatment of keloid fibroblasts. The 17-AAG–treated keloid fibroblasts had less directionality to the wound center and migrated a shorter distance. Conclusions: The authors confirmed that the inhibition of heat shock protein 90 in keloid fibroblasts could promote apoptosis and attenuate proliferation and migration of keloid fibroblasts. Therefore, the authors think that the inhibition of heat shock protein 90 is a key factor in the regulation of biological processes in keloids. With further preclinical study, the authors will be able to apply these results clinically for keloid treatment. Abstract : Supplemental Digital Content is available in the text.